Analisis Bias Gender Dalam Iklan Super Pell - Muhammad Eko Riyadi; Rini Sulastri (Gunung Djati Conference Series, 2024)
The media in its development has its own influence on people's point of view. Likewise, gender issues are also part of the media scheme itself. This article discusses gender issues, namely gender bias in the advertising media for the television show "Super Pell" using sociological analysis in it. This research uses qualitative research methodology with a qualitative descriptive approach. Qualitative research methodology that uses secondary data sources, in the form of a study of literature related to the problem or juduk in this article in the form of books, journal articles, and other data sources. The results of the research are gender equality and gender injustice or imbalance. Women can be able to do work outside the domestic, but because of the patriarchal culture are still placed as households.